Kombinasi Ekstrak Etanol Buah Mengkudu (Morinda citrifolia L.) dan Daun Pepaya (Carica papaya L.) sebagai Hepatoprotektif selama Pengobatan Tuberkulosis - TITIK SUNARNI; RINI PRASTIWI; MARDIYONO MARDIYONO; YUDI RINANTO (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Hepatoprotective activity of Morinda citrifolia L. fruits and Carica papaya L. leaves ethanolic extract have been investigated in antituberculosis-induced rats. Forty rats were divided into following eight groups: normal control group was treated with normal feed and water; negative control group was treated with isoniazid and rifampicin, positive control group was treated with isoniazid, rifampicin and Methicol®, and the last five groups were treated with isoniazid, rifampicin and combination of M. citrifolia L. fruits and C. papaya L. leaves extract on various doses. All groups were treated daily for 27 days. Serum levels of bilirubin, alanine aminotransferase (ALT) as well as aspartate aminotransferase (AST) were determined on day -0, 14, 21 and 28 to monitor the liver function. All rats were sacrified on day-28 for liver histology observation. Combination of M. citrifolia extract 20 mg/200 g bw and C. papaya extract 120 mg/200 g bw significantly decreased the serum level of ALT, AST as well as bilirubin. The histology study showed that this combination could prevent the liver damaged based on the lower percentage of necrosis (27.83%), as compared to that of negative control (47.47%).